Molecular Docking Study: Phyllanthus niruri L.'s Active Compounds as Dengue Haemorrhagic Fever Therapy - Riska Prasetiawati; Silviyanita Isna Seftila; Benny Permana; Novriyanti Lubis (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Dengue Haemorrhagic Fever is a disease caused by the dengue virus through a mosquito vector Aedesaegypti. NS3 Helicase is known as one of nonstructural proteins consisting of some essential enzymesfor virus replication. Nowadays ivermectin has been developed as an anti-dengue haemorrhagic feverwith therapy target NS3 Helicase. The therapeutics drug for dengue haemorrhagic fever has not beenfound specifically. Methanol extract of meniran (Phyllanthus niruri L.) reported the activity to denguevirus with a concentration of 15,63 μg/mL. This research aimed to study the interactions and affinityof the active compound of meniran with the receptor (NS3 Helicase) and to know ADME and toxicityprofile. From 56 active compounds of meniran, there was one best candidate as dengue haemorrhagicfever therapy which has energy binding (ΔG) and Inhibition Constanta (IC) lower than native ligandand ivermectin, it is nirurin with energy binding -4.87 kcal/mol. These candidate compounds havegood absorption and distribution profiles so they are thought to be candidates for dengue fever therapyby targeting the NS3 Helicase receptor which is better than ivermectin and native ligands.